1996
DOI: 10.1247/csf.21.245
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes at the Site of Tritrichomonas foetus-Erythrocyte Interaction.

Abstract: ABSTRACT. Tritrichomonas foetus strongly agglutinates human erythrocytes, thus suggesting the occurrence of an adhesin associated with its surface. Adherencewas observed immediately after mixing of the parasites with erythrocytes and the intensity increased for up to 30 min. Scanning electron microscopy examination of T. foetus-erythrocytes attachment showed that trichomonad cytoadherence took place mainly through their anterior and recurrent flagella. Ultrastructural observations showed that T. foetus contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Da Silva et al [5] showed strong agglutination between T. foetus and human A group erythrocytes, suggesting the occurrence of an adhesin associated with the parasite surface. Indeed, the authors used the same K strain and human erythrocytes that we used in the present study and observed an increasing intensity of adhesion for up to 30 min of incubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Da Silva et al [5] showed strong agglutination between T. foetus and human A group erythrocytes, suggesting the occurrence of an adhesin associated with the parasite surface. Indeed, the authors used the same K strain and human erythrocytes that we used in the present study and observed an increasing intensity of adhesion for up to 30 min of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CP inhibitors greatly reduce erythrocyte lysis, suggesting that CP may be a lytic factor involved in hemolysis [6]. Furthermore, studies focusing on the trichomonad-cell interaction have pointed out that the parasites can exert their cytopathic effects through: (a) physical contact established between the two cell surfaces, (b) toxins released from parasites into the interaction media, or (c) the association of both mechanisms [5].…”
Section: Discussionmentioning
confidence: 99%
“…Many molecules are thought to be involved in the adhesion processes of trichomonads. These include a glycoprotein present in T. foetus that recognizes sialic acid on the surface of target cells (Bonilha et al 1995;, adhesin-like proteins which promote hemaglutination in T. foetus (Da Silva et al 1996Silva et al , 1999, manose residues and other sugars and glycoconjugates located on the surface of T. foetus and/or Trichomonas vaginalis (Cappuccinelli et al 1975;Mirhaghani and Warton 1998;Benchimol and Bernardino 2002).…”
Section: Trophozoite Vs Pseudocyst Adhesion and Tf190 Expressionmentioning
confidence: 99%
“…In the case of Tritrichomonas foetus, which is a protozoan found in the urogenital tract of cattle, there is very little information on basic aspects of the process of its interaction with cells from the host, although there are reports on the presence of receptors for extracellular-matrix proteins (Bonilha and Silva Filho 1990;). It has previously been shown that T. foetus, but not T. vaginalis, displays a high level of hemagglutinating activity and that during this process a focal adhesion, with changes in the structural organization of the plasma membrane, takes place (Silva et al 1996).This observation suggests that on its surface, T. foetus exposes molecules with an adhesin-like activity. In the present study we further analyzed this question and obtained evidence indicating the presence of a parasite surface protein with adhesin activity.…”
Section: Introductionmentioning
confidence: 95%
“…Tritrichomonas foetus (K strain) was maintained in TYM medium at 37°C (Diamond 1957) as previously described (Silva et al 1996).…”
Section: Microorganismmentioning
confidence: 99%